Increasing students' interest and knowledge about herbs in elementary school - Devi Anggraini Putri; Riyadatus Solihah; Rizka Efi Mawli (University of Merdeka Malang, 2022)
Herbs is not only a potent Indonesian herbal medicine but also the ancestor tried to keep the preservation of herbs. Therefore, knowledge about herbs is important to be preserved from an early age. However, currently, the interest of Indonesian children in consuming herbs tends to decrease. The stigma that herbs is bitter is the reason why herbs is unlikeable. Based on the analysis of the demographic condition in Bangkalan, the quality of education is still low, interest and knowledge about herbs is also low. The purpose of this program is to increase students' interest and knowledge about herbs at SDN Demangan 3 Bangkalan. The methods are socializing, implementing educational games about herbs, and drinking herbs together. Furthermore, students' interest in herbs was evaluated by using a questionnaire. Meanwhile, students' knowledge about herbs was analyzed and evaluated based on the results of the pre-test and post-test. The results of the program showed that students’ interest in herbs increased by 83% after a learning media namely herbs snake ladder game was applied. In addition, students' knowledge about herbs also increased by 76% from 24 respondents. Thus, this program is recommended to increase the interest and knowledge of elementary school students about herbs.